Predicting Oral HIV Pre‐Exposure Prophylaxis Efficacy in Cisgender Women Across Pregnancy and Postpartum - Yifan Yu; Kristina M. Brooks; Gustavo F. Doncel; Brookie M. Best; Mark A. Marzinke; Mark Mirochnick; Peter L. Anderson; Landon Myer; Connie Celum; Renee Heffron; Jenell Coleman; Dvora L. Joseph Davey; et al. (The Journal of Clinical Pharmacology, 2026)
Abstract Cisgender women face an increased risk of HIV acquisition during pregnancy and postpartum. Oral pre‐exposure prophylaxis (PrEP) with emtricitabine and tenofovir disoproxil fumarate (F/TDF) is recommended in pregnancy despite limited published pharmacokinetic (PK) and efficacy data during pregnancy. Altered PK during pregnancy may reduce prophylactic efficacy and necessitate higher adherence. Tenofovir alafenamide (TAF) is a newer tenofovir prodrug with higher tenofovir diphosphate (TFV‐DP) exposure in peripheral blood mononuclear cells (PBMCs), but the prophylactic efficacy of F/TAF across different reproductive stages in women is understudied. We adapted a multiscale modeling framework to predict the prophylactic efficacy of F/TDF and F/TAF across varying adherence levels and during the second trimester, third trimester, and 6–12 weeks postpartum. Clinical trial simulations were conducted utilizing PBMC TFV‐DP and emtricitabine triphosphate concentrations as surrogate markers for F/TAF and F/TDF efficacy. For both F/TDF and F/TAF, prophylactic efficacy was lowest during the second trimester, increased in the third trimester (but remained below nonpregnant levels), and was highest postpartum. At high adherence levels of five or more pills per week, predicted effectiveness remained high across pregnancy and postpartum and effectiveness exceeded 97% for both regimens, with maximum decreases in the second trimester of only 0.9 percent point for F/TDF and 0.3 percent point for F/TAF. These findings suggest that adherence is the primary determinant of PrEP effectiveness during pregnancy and postpartum, while pregnancy‐related PK changes have a limited impact on efficacy.